Preparation method of CsPbBr3 composite luminescent material based on perovskite
Through the liquid phase synthesis method of lead-free perovskite precursor and green solvent and vacuum low-temperature drying technology, the problem of toxic solvents and particles agglomeration in the preparation of perovskite nanocrystals is solved, and efficient and environmentally friendly perovskite composite luminescence is achieved. Material preparation improves optical performance and safety.
Patent Information
- Application Number
- CN202411334157.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
AI Technical Summary
The use of toxic organic solvents in the existing perovskite nanocrystal preparation methods leads to environmental pollution and health risks, and the grinding process leads to particle agglomeration that affects optical properties.
The lead-free perovskite precursor is mixed with a green solvent, and reacts under controlled temperature and pressure through liquid phase synthesis to inhibit particle agglomeration, and particle size uniformity and optical performance are ensured through vacuum low-temperature drying and ultrasonic dispersion technology.
The preparation of environmentally friendly and non-toxic perovskite composite luminescent materials is realized, which improves the optical performance and safety of the materials and reduces environmental and health risks.
Smart Images

Figure CN119193155A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of luminescent materials, and in particular to a method for preparing a composite luminescent material based on perovskite CsPbBr3. Background Art
[0002] Perovskite nanocrystals are ionic crystals with advantages such as low formation energy and high defect tolerance. Based on the above characteristics, many synthesis methods have been developed. At present, colloidal synthesis method occupies a dominant position in the preparation of perovskite nanocrystals. The advantages and disadvantages of this method are obvious: the controllable growth process can easily obtain nanoparticles with uniform particle size distribution, so that the nanocrystals have narrow emission peak width, high fluorescence intensity and color gamut; however, a large amount of toxic organic solvents are used in the synthesis and purification process, and a large amount of organic waste liquid is generated, which not only damages the health of the synthesizers but also causes serious environmental problems. Therefore, from an environmental perspective, the colloidal synthesis method is not a green method. Template synthesis method, as an alternative to colloidal synthesis method, omits the subsequent purification step and greatly reduces the use of toxic solvents, but still cannot avoid the use of organic solvents. In recent years, some researchers have also used mechanical grinding method to prepare perovskite nanocrystals from top to bottom, which avoids the use of organic solvents. However, in order to obtain high quantum efficiency products, organic ligands such as oleic acid and oleylamine are still needed to inhibit the agglomeration and growth of nanocrystals, and this method has high requirements for equipment.
[0003] In order to solve the defects of the prior art, a technical solution with publication number CN 111961467A was found after searching. The preparation method of the perovskite composite luminescent material comprises the steps of: solid-phase mixing the perovskite precursor and the metal halide according to a molar ratio of 1:0.1-100; melting the solid-phase mixture at 650-1000°C for 10-60 minutes, cooling and crystallizing, and grinding to a particle size of less than 80μm to obtain the perovskite composite luminescent material. Different from the prior art, the method of the present invention has the characteristics of simple synthesis process, low cost, and no use of solvents. The prepared luminescent material has high luminescent intensity and high luminescent color purity, and can be widely used in photoluminescent devices, lasers, and nonlinear optical devices.
[0004] However, the process of grinding to a particle size of less than 80μm will cause particle agglomeration or inhomogeneity, affecting the optical properties and application effects of the material. At the same time, the lead halide in the formula is toxic and poses a potential threat to human health and the ecosystem. The intake of lead may cause neurological damage, developmental problems and other health problems. Summary of the invention
[0005] Technical issues solved:
[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a composite luminescent material based on perovskite CsPbBr3, which has the advantages of uniform particle agglomeration during the preparation process, improving the optical properties of the finished material, and being more environmentally friendly and green in production without the presence of toxic substances that harm the environment and human body, thereby solving the problems of the above-mentioned technologies.
[0007] Technical solution:
[0008] To achieve the above object, the present invention provides the following technical solution: a method for preparing a composite luminescent material based on perovskite CsPbBr3, comprising the following steps:
[0009] Step 1: Precursor dissolution: The lead-free perovskite precursor is mixed with a green solvent to form a solution in which the precursor is completely dissolved and the solution is clear and transparent without suspended particles or turbidity;
[0010] Step 2, liquid phase synthesis: adopt liquid phase synthesis method: solvothermal method or hydrothermal method, react under controlled temperature and pressure to promote the crystallization of CsSnBr3 and inhibit particle agglomeration; the reaction conditions are set at 150-200 ° C, and the reaction time is 6-12 hours;
[0011] Step 3: Cooling and washing: After the reaction is completed, the reaction system is allowed to cool naturally to room temperature (32-36°C); unreacted precursors and impurities are removed by centrifugation and washing;
[0012] Step 4: Drying and grinding: Dry the cleaned solid sample at low temperature in vacuum to remove the residual solvent, and grind the sample at a low speed of 30 rpm using a ball mill to control the particle size to ensure that it is less than 80 μm, while reducing particle agglomeration;
[0013] Step 5: Uniform dispersion: The dried particles are uniformly dispersed by using an ultrasonic dispersion method to uniformly disperse the particles in a suitable green carrier, including water or ethanol;
[0014] Step 6: Forming a thin film: coating the dispersion on the substrate, using spin coating or other techniques to form a uniform thin film;
[0015] Step 7: Drying and curing: The coated substrate is dried and cured at a temperature of 60°C-120°C to ensure the optical properties of the material.
[0016] Preferably, the detailed steps of the solvothermal method in step 2 are:
[0017] S1.1. Material preparation: Prepare precursors: cesium chloride CsCl, tin chloride SnCl2 and bromide such as KBr or NaBr, and select a suitable organic solvent: dimethyl sulfoxide DMSO or ethanol;
[0018] S1.2, dissolving the precursor: dissolving the precursor in a selected organic solvent;
[0019] S1.3, reaction setting: transfer the solution to a high pressure reactor, seal it and set the reaction temperature to 150-200°C, and the reaction time to 6-12 hours;
[0020] S1.4, reaction process: heating the reactor to the set temperature, under which condition, CsSnBr3 begins to crystallize and particle agglomeration is suppressed;
[0021] S1.5, cooling and collection: after the reaction is completed, slowly cool the reactor to room temperature, open the reactor, and take out the reaction product;
[0022] S1.6. Washing and drying: Wash the product with deionized water or a suitable solvent to remove unreacted precursors and impurities, and dry the washed product in a vacuum drying oven to obtain CsSnBr3 powder.
[0023] Preferably, the detailed steps of the hydrothermal method in step 2 are:
[0024] S2.1. Material preparation: Prepare precursors: cesium chloride CsCl, tin chloride SnCl2 and bromide such as KBr or NaBr, and use deionized water as the reaction medium;
[0025] S2.2, dissolving the precursor: dissolving the precursor in deionized water, ensuring complete dissolution to form a uniform aqueous solution;
[0026] S2.3, reaction setting: transfer the solution to a hydrothermal reactor, seal it, set the reaction temperature to 150-200°C, and the reaction time to 6-12 hours;
[0027] S2.4, Reaction process: Heat the hydrothermal reactor to the set temperature. Under this condition, CsSnBr3 begins to crystallize while inhibiting particle agglomeration.
[0028] S2.5, cooling and collection: after the reaction is completed, slowly cool the reactor to room temperature, open the reactor, and take out the reaction product;
[0029] S2.6. Washing and drying: Wash the product with deionized water to remove unreacted precursors and impurities, and dry the washed product in a vacuum drying oven to obtain CsSnBr3 powder.
[0030] Preferably, the complete dissolution expression of the precursor in step 1 is:
[0031] C D ≈C P
[0032] Among them, C Drepresents the actual concentration of the precursor in the solution, C P represents the initial concentration of the precursor;
[0033] The clear and transparent state of the solution is expressed as:
[0034] T≈100%
[0035] Wherein, T represents the transmittance percentage of the solution.
[0036] Preferably, the reaction temperature and time in step 2 are expressed as:
[0037] T∈[150℃,200℃]
[0038] t∈[6h,12h]
[0039] Promote CsSnBr3 crystallization and inhibit particle agglomeration:
[0040] The crystallization process is represented by the crystallization rate R, which should be high enough to promote the crystallization of CsSnBr3, uniform particle size distribution D, and reduce particle agglomeration. The expression is:
[0041] R≥R min
[0042] D≤D max
[0043] Among them, R min Indicates the minimum crystallization rate, D max Indicates the maximum allowable particle size to reduce particle agglomeration.
[0044] Preferably, the cooling temperature expression in step 3 is:
[0045] T cooling ∈[32℃,36℃]
[0046] Among them, T cooling Indicates the temperature after cooling.
[0047] Preferably, the centrifugal expression in step 3 is:
[0048] C premaining ≈0
[0049] C impurities ≈0
[0050] Where: C premaining represents the concentration of unreacted precursor after centrifugation, C impurities Indicates the concentration of impurities after centrifugation, close to 0.
[0051] Preferably, the drying expression in step 4 is:
[0052] P vacuum <P atm
[0053] T drying <T ambient
[0054] Among them, P vacuum Indicates the vacuum drying pressure, which should be lower than the atmospheric pressure P atm ; T drying Indicates the drying temperature, which should be lower than room temperature T ambient .
[0055] Preferably, the grinding expression in step 4 is:
[0056] D particle ≤80μm
[0057] C agglomeration ≈0
[0058] Among them, D particle Indicates the particle size after grinding, C agglomeration Indicates the degree of particle agglomeration, close to 0.
[0059] Preferably, the uniform dispersion processing expression in step 5 is:
[0060] C uniform =C target
[0061] Among them, C uniform Indicates the uniformity of the concentration distribution of particles in the carrier, C target Indicates the target uniform concentration;
[0062] The ultrasonic dispersion expression is:
[0063] E sonication ≥E min
[0064] Where: E sonication Indicates the ultrasonic treatment energy, E min Represents the minimum energy required to ensure uniform dispersion of particles.
[0065] Compared with the prior art, the present invention provides a method for preparing a composite luminescent material based on perovskite CsPbBr3, which has the following beneficial effects:
[0066] 1. The present invention effectively promotes the crystallization of CsSnBr3 and inhibits the agglomeration of particles by setting appropriate reaction temperature T∈[150℃, 200℃] and reaction time t∈[6h, 12h], and achieves a high crystallization rate R≥R mIt helps to form uniform particles, and the appropriate particle size distribution D≤D m Reduce particle agglomeration, thereby improving the optical properties of the material, control cooling to 32℃-36℃ to ensure the stability of the crystal structure, avoid stress and defects caused by rapid cooling, which helps to maintain the optical properties of the material. premaining ≈0 and washing to remove unreacted precursors and impurities, reducing the negative impact on the optical properties of the material, ensuring that the final particles are pure and uniform, and drying under vacuum and low temperature to effectively remove residual solvents, avoiding particle agglomeration or unevenness caused by solvent volatilization, and using 30rpm low-speed grinding to ensure that the particle size is less than 80μm, while reducing particle agglomeration, which helps to improve the uniformity and optical properties of the material, achieving the beneficial effect of uniform particle agglomeration in the preparation process and improving the optical properties of the finished material.
[0067] 2. The present invention uses a lead-free perovskite precursor in the preparation process of the material, which means that toxic heavy metals such as lead are not used, thus avoiding the generation of toxic substances from the source. Alternatives to lead-based perovskites, such as CsPbBr3, reduce environmental and health risks. In the precursor dissolution step, green solvents are used: water or ethanol. These solvents are more environmentally friendly than traditional organic solvents: chloroform and benzene, with lower toxicity and better biodegradability. Ethanol and deionized water are both relatively safe solvents with less harm to the environment and human body. In the solvent thermal method or hydrothermal method in the liquid phase synthesis process, the reaction temperature is controlled at 150-200°C and the time is controlled at 6-12 hours, and the reaction can be completed under relatively mild conditions. Lower temperature and pressure conditions reduce the need for high-temperature and high-pressure equipment, help reduce energy consumption and reduce possible harmful gas emissions. In the cooling and washing steps, deionized water is used to wash the product. Deionized water is non-toxic and does not introduce additional pollutants. This practice helps reduce environmental pollution and potential harm to the human body. The use of vacuum low-temperature drying method avoids toxic chemicals that may be used in traditional drying methods. Vacuum drying helps reduce the release of volatile organic compounds (VOCs), is more environmentally friendly, and achieves the beneficial effect of more environmentally friendly and green production without the presence of toxic substances that harm the environment and the human body. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 It is a schematic diagram of the method of the present invention; DETAILED DESCRIPTION
[0069] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0070] See also Figure 1 , a method for preparing a composite luminescent material based on perovskite CsPbBr3, comprising the following steps:
[0071] Step 1: Precursor dissolution: The lead-free perovskite precursor is mixed with a green solvent to form a solution in which the precursor is completely dissolved and the solution is clear and transparent without suspended particles or turbidity;
[0072] Step 2, liquid phase synthesis: adopt liquid phase synthesis method: solvothermal method or hydrothermal method, react under controlled temperature and pressure to promote the crystallization of CsSnBr3 and inhibit particle agglomeration; the reaction conditions are set at 150-200 ° C, and the reaction time is 6-12 hours;
[0073] Step 3: Cooling and washing: After the reaction is completed, the reaction system is allowed to cool naturally to room temperature (32-36°C); unreacted precursors and impurities are removed by centrifugation and washing;
[0074] Step 4: Drying and grinding: Dry the cleaned solid sample at low temperature in vacuum to remove the residual solvent, and grind the sample at a low speed of 30 rpm using a ball mill to control the particle size to ensure that it is less than 80 μm, while reducing particle agglomeration;
[0075] Step 5: Uniform dispersion: The dried particles are uniformly dispersed by using an ultrasonic dispersion method to uniformly disperse the particles in a suitable green carrier, including water or ethanol;
[0076] Step 6: Forming a thin film: coating the dispersion on the substrate, using spin coating or other techniques to form a uniform thin film;
[0077] Step 7: Drying and curing: The coated substrate is dried and cured at a temperature of 60°C-120°C to ensure the optical properties of the material.
[0078] Lead-free perovskite precursors are used in the preparation of the materials, which means that toxic heavy metals such as lead are not used, avoiding the production of toxic substances at the source. Alternatives to lead-based perovskites, such as CsPbBr3, reduce environmental and health risks. In the precursor dissolution step, green solvents are used: water or ethanol. These solvents are more environmentally friendly than traditional organic solvents: chloroform and benzene, with lower toxicity and better biodegradability. Ethanol and deionized water are relatively safe solvents with less harm to the environment and human body. In the solvothermal method or hydrothermal method in the liquid phase synthesis process, the reaction temperature is controlled at 150-200°C and the time is controlled at 6-12 hours, which can complete the reaction under relatively mild conditions. Lower temperature and pressure conditions reduce the need for high-temperature and high-pressure equipment, helping to reduce energy consumption and possible harmful gas emissions. During the cooling and washing steps, deionized water is used to wash the product. Deionized water is non-toxic and does not introduce additional pollutants. This practice helps reduce environmental pollution and potential harm to the human body. The use of vacuum low-temperature drying method avoids toxic chemicals that may be used in traditional drying methods. Vacuum drying helps reduce the release of volatile organic compounds (VOCs).
[0079] Specifically, the detailed steps of the solvothermal method in step 2 are:
[0080] S1.1. Material preparation: Prepare precursors: cesium chloride CsCl, tin chloride SnCl2 and bromide such as KBr or NaBr, and select a suitable organic solvent: dimethyl sulfoxide DMSO or ethanol;
[0081] S1.2, dissolving the precursor: dissolving the precursor in a selected organic solvent;
[0082] S1.3, reaction setting: transfer the solution to a high pressure reactor, seal it and set the reaction temperature to 150-200°C, and the reaction time to 6-12 hours;
[0083] S1.4, reaction process: heating the reactor to the set temperature, under which condition, CsSnBr3 begins to crystallize and particle agglomeration is suppressed;
[0084] S1.5, cooling and collection: after the reaction is completed, slowly cool the reactor to room temperature, open the reactor, and take out the reaction product;
[0085] S1.6. Washing and drying: Wash the product with deionized water or a suitable solvent to remove unreacted precursors and impurities, and dry the washed product in a vacuum drying oven to obtain CsSnBr3 powder.
[0086] Specifically, the detailed steps of the hydrothermal method in step 2 are:
[0087] S2.1. Material preparation: Prepare precursors: cesium chloride CsCl, tin chloride SnCl2 and bromide such as KBr or NaBr, and use deionized water as the reaction medium;
[0088] S2.2, dissolving the precursor: dissolving the precursor in deionized water, ensuring complete dissolution to form a uniform aqueous solution;
[0089] S2.3, reaction setting: transfer the solution to a hydrothermal reactor, seal it, set the reaction temperature to 150-200°C, and the reaction time to 6-12 hours;
[0090] S2.4, Reaction process: Heat the hydrothermal reactor to the set temperature. Under this condition, CsSnBr3 begins to crystallize while inhibiting particle agglomeration.
[0091] S2.5, cooling and collection: after the reaction is completed, slowly cool the reactor to room temperature, open the reactor, and take out the reaction product;
[0092] S2.6. Washing and drying: Wash the product with deionized water to remove unreacted precursors and impurities, and dry the washed product in a vacuum drying oven to obtain CsSnBr3 powder.
[0093] Specifically, the complete dissolution expression of the precursor in step 1 is:
[0094] C D ≈C P
[0095] Among them, C D represents the actual concentration of the precursor in the solution, C P represents the initial concentration of the precursor;
[0096] The clear and transparent state of the solution is expressed as:
[0097] T≈100%
[0098] Wherein, T represents the transmittance percentage of the solution.
[0099] Specifically, the reaction temperature and time in step 2 are expressed as:
[0100] T∈[150℃,200℃]
[0101] t∈[6h,12h]
[0102] Promote CsSnBr3 crystallization and inhibit particle agglomeration:
[0103] The crystallization process is represented by the crystallization rate R. The crystallization rate should be high enough to promote the crystallization of CsSnBr3, make the particle size distribution D uniform, and reduce the particle agglomeration phenomenon. The expression is:
[0104] R≥R min
[0105] D≤D max
[0106] Among them, R min Indicates the minimum crystallization rate, D max Indicates the maximum allowable particle size to reduce particle agglomeration.
[0107] Specifically, the cooling temperature expression in step 3 is:
[0108] T cooling ∈[32℃,36℃]
[0109] Among them, T cooling Indicates the temperature after cooling.
[0110] Specifically, the centrifugal expression in step 3 is:
[0111] C premaining ≈0
[0112] C impurities ≈0
[0113] Where: C premaining represents the concentration of unreacted precursor after centrifugation, C impurities Indicates the concentration of impurities after centrifugation, close to 0.
[0114] Specifically, the drying expression in step 4 is:
[0115] P vacuum <P atm
[0116] T drying <T ambient
[0117] Among them, P vacuum Indicates the vacuum drying pressure, which should be lower than the atmospheric pressure P atm ; T drying Indicates the drying temperature, which should be lower than room temperature T ambient .
[0118] Specifically, the grinding expression in step 4 is:
[0119] D particle ≤80μm
[0120] C agglomeration ≈0
[0121] Among them, D particle Indicates the particle size after grinding, C agglomeration Indicates the degree of particle agglomeration, close to 0.
[0122] Specifically, the uniform dispersion processing expression in step 5 is:
[0123] C uniform =C target
[0124] Among them, C uniform Indicates the uniformity of the concentration distribution of particles in the carrier, C target Indicates the target uniform concentration;
[0125] The ultrasonic dispersion expression is:
[0126] E sonication ≥E min
[0127] Where: E sonication Indicates the ultrasonic treatment energy, E min Represents the minimum energy required to ensure uniform dispersion of particles.
[0128] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and alterations may be made to the embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a composite luminescent material based on perovskite CsPbBr3, characterized in that: The following steps are involved: Step 1: Precursor dissolution: The lead-free perovskite precursor is mixed with a green solvent to form a solution in which the precursor is completely dissolved and the solution is clear and transparent without suspended particles or turbidity; Step 2, liquid phase synthesis: adopt liquid phase synthesis method: solvothermal method or hydrothermal method, react under controlled temperature and pressure to promote the crystallization of CsSnBr3 and inhibit particle agglomeration; the reaction conditions are set at 150-200 ° C, and the reaction time is 6-12 hours; Step 3: Cooling and washing: After the reaction is completed, the reaction system is allowed to cool naturally to room temperature (32-36°C); unreacted precursors and impurities are removed by centrifugation and washing; Step 4: Drying and grinding: Dry the cleaned solid sample at low temperature in vacuum to remove the residual solvent, and grind the sample at a low speed of 30 rpm using a ball mill to control the particle size to ensure that it is less than 80 μm, while reducing particle agglomeration; Step 5: Uniform dispersion: The dried particles are uniformly dispersed by using an ultrasonic dispersion method to uniformly disperse the particles in a suitable green carrier, including water or ethanol; Step 6: Forming a thin film: coating the dispersion on the substrate, using spin coating or other techniques to form a uniform thin film; Step 7: Drying and curing: The coated substrate is dried and cured at a temperature of 60°C-120°C to ensure the optical properties of the material.
2. A method for preparing a composite luminescent material based on perovskite CsPbBr3 according to claim 1, characterized in that: The detailed steps of the solvothermal method in step 2 are as follows: S1.
1. Material preparation: Prepare precursors: cesium chloride CsCl, tin chloride SnCl2 and bromide such as KBr or NaBr, and select a suitable organic solvent: dimethyl sulfoxide DMSO or ethanol; S1.2, dissolving the precursor: dissolving the precursor in a selected organic solvent; S1.3, reaction setting: transfer the solution to a high pressure reactor, seal it and set the reaction temperature to 150-200°C, and the reaction time to 6-12 hours; S1.4, reaction process: heating the reactor to the set temperature, under which condition, CsSnBr3 begins to crystallize and particle agglomeration is suppressed; S1.5, cooling and collection: after the reaction is completed, slowly cool the reactor to room temperature, open the reactor, and take out the reaction product; S1.
6. Washing and drying: Wash the product with deionized water or a suitable solvent to remove unreacted precursors and impurities, and dry the washed product in a vacuum drying oven to obtain CsSnBr3 powder.
3. The method for preparing a composite luminescent material based on perovskite CsPbBr3 according to claim 1, characterized in that: The detailed steps of the hydrothermal method in step 2 are as follows: S2.
1. Material preparation: Prepare precursors: cesium chloride CsCl, tin chloride SnCl2 and bromide such as KBr or NaBr, and use deionized water as the reaction medium; S2.2, dissolving the precursor: dissolving the precursor in deionized water, ensuring complete dissolution to form a uniform aqueous solution; S2.3, reaction setting: transfer the solution to a hydrothermal reactor, seal it, set the reaction temperature to 150-200°C, and the reaction time to 6-12 hours; S2.4, Reaction process: Heat the hydrothermal reactor to the set temperature. Under this condition, CsSnBr3 begins to crystallize while inhibiting particle agglomeration. S2.5, cooling and collection: after the reaction is completed, slowly cool the reactor to room temperature, open the reactor, and take out the reaction product; S2.
6. Washing and drying: Wash the product with deionized water to remove unreacted precursors and impurities, and dry the washed product in a vacuum drying oven to obtain CsSnBr3 powder.
4. The method for preparing a composite luminescent material based on perovskite CsPbBr3 according to claim 1, characterized in that: The complete dissolution expression of the precursor in step 1 is: C D ≈C P Among them, C D represents the actual concentration of the precursor in the solution, C P represents the initial concentration of the precursor; The clear and transparent state of the solution is expressed as: T≈100% Wherein, T represents the transmittance percentage of the solution.
5. A method for preparing a composite luminescent material based on perovskite CsPbBr3 according to claim 4, characterized in that: The reaction temperature and time in step 2 are expressed as: T∈[150℃,200℃] t∈[6h,12h] Promote CsSnBr3 crystallization and inhibit particle agglomeration: The crystallization process is represented by the crystallization rate R, which should be high enough to promote the crystallization of CsSnBr3, uniform particle size distribution D, and reduce particle agglomeration. The expression is: R≥R min D≤D max Among them, R min Indicates the minimum crystallization rate, D max Indicates the maximum allowable particle size to reduce particle agglomeration.
6. A method for preparing a composite luminescent material based on perovskite CsPbBr3 according to claim 5, characterized in that: The cooling temperature expression in step 3 is: T cooling ∈[32℃,36℃] Among them, T cooling Indicates the temperature after cooling.
7. A method for preparing a composite luminescent material based on perovskite CsPbBr3 according to claim 6, characterized in that: The centrifugal expression in step 3 is: C premaining ≈0 C impurities ≈0 Where: C premaining represents the concentration of unreacted precursor after centrifugation, C impurities Indicates the concentration of impurities after centrifugation, close to 0.
8. The method for preparing a composite luminescent material based on perovskite CsPbBr3 according to claim 7, characterized in that: The drying expression in step 4 is: P vacuum <P atm T drying <T ambient Among them, P vacuum Indicates the vacuum drying pressure, which should be lower than the atmospheric pressure P atm ; T drying Indicates the drying temperature, which should be lower than room temperature T ambient .
9. A method for preparing a composite luminescent material based on perovskite CsPbBr3 according to claim 8, characterized in that: The grinding expression in step 4 is: D particle ≤80μm C agglomeration ≈0 Among them, D particle Indicates the particle size after grinding, C agglomeration Indicates the degree of particle agglomeration, close to 0.
10. A method for preparing a composite luminescent material based on perovskite CsPbBr3 according to claim 9, characterized in that: The uniform dispersion processing expression in step 5 is: C uniform =C target Among them, C uniform Indicates the uniformity of the concentration distribution of particles in the carrier, C target Indicates the target uniform concentration; The ultrasonic dispersion expression is: AND sonication ≥E min Where: E sonication Indicates the ultrasonic treatment energy, E min Represents the minimum energy required to ensure uniform dispersion of particles.
